Can There Be Growth with Equity? An Initial Assessment of Land Reform in South Africa - Deininger, Klaus (World Bank, Washington, DC, 2015)
The authors use evidence from a survey of about 1200 beneficiaries of South African land reform to assess the performance of the initial phase of the land reform program. They find that the program has not lived up to the quantitative goals set, but did successfully target the poor. It has led to a significant number of economically successful projects that already generate sustainable revenues. These projects have involved significantly larger shares of poor people than less viable projects, suggesting that increased access to productive assets could be an important path to poverty reduction. Given the need to develop a diverse and less subsidy-dependent strategy for poverty reduction, suitably adapted land reform could play an important part in restructuring South Africa's rural sector. Much of this potential has yet to be realized. The author's analysis points toward clear lessons about program design: 1) Increase beneficiary awareness and participation. Shift from a centralized, bureaucratic structure designed for land distribution toward seeing program components as part of an integrated vision of rural development. This would strengthen links to other parts of land reform (including tenure reform), make better use of local synergies (including infrastructure such as housing), and encourage rather than stifle local initiative decentralized implementation mechanisms. 2) Integrate land redistribution into a land policy framework that strengthens existing property rights, especially tenure security for residents of communal areas. 3) Ensure transparency, accountability, and the participation of the private sector. These are essential for dispelling fears that land reform is just another means of political favoritism rather than an instrument to transform the rural sector, as is indeed supported by international evidence.